Poland's economic and social transformation 1989-2014 and contemporary challenges - Stanislaw Gomulka (Central Bank Review (CBR), 2016)
The article has two objectives. The first one is to identify the distinctive features of the Polish transformation, especially those which may explain why the initial, transformational recession was less serious than elsewhere and why the subsequent economic growth was relatively high. It discusses positive as well as negative effects of the transition to the market-based economy. Some popular extremely negative evaluations of the transition are argued to be at variance with facts. The other objective is to discuss the reforms and policies necessary for Poland to continue the process of catching up with the most advanced countries, so that the civilisation gap is further bridged or possibly eliminated.
Keywords: 330; Poland; Economic and social transformation; Transformation recession